„Odnowa”, „Osnowy Literackie”, „Wymiary” (1938–1939): wybory literackie orężem w budowaniu odrodzonej Ojczyzny? - Małgorzata Bańkowska; Magdalena Przybysz-Stawska (Z Badań nad Książką i Księgozbiorami Historycznymi, 2020)
Two decades after independence recovering Polish intellectuals and writers were looking for new Poland ideal form. Close to the end of the thirties in twentieth century, in view of unstable situation in Poland and into the world, book and press became important tool for promotion of political and cultural ideas coming from different political groups. Taking into account this perspective special attention should pay on the editorial and literary organisation, developed fast in last years before the World War II. The aim of this presentation is to show the role of local social and literary journals from Lodz area (“Odnowa”, “Osnowy Literackie”, “Wymiary”), issued just before WWII, in creating of cultural and social attitude. It will be analyse 20 numbers of selected periodicals, covered years 1938-1939. The collected material will be used to find answers for below listed questions: how literal taste of readers was formed; how the selected journals met needs of society in the area of culture and ideology; in this very important moment for Poland.